An Augmented-Reality Holographic Stereogram Based on 3D Optical Field Information Manipulation and Reconstruction - Liu, Yunpeng; Jing, Tao; Qu, Qiang; Zhang, Ping; Li, Pei; Yang, Qian; Jiang, Xiaoyu; Yan, Xingpeng (Frontiers in Physics, 2022)
Holographic stereogram comprises a hotspot in the field of three-dimensional (3D) display. It can reconstruct the light field information of real and virtual scenes at the same time, further improving the comprehensibility of the scene and achieving the “augmentation” of the scene. In this paper, an augmented reality-holographic stereogram based on 3D reconstruction is proposed. First, the point cloud data is generated by VisualSFM software, and then the 3D mesh model is reconstructed by MeshLab software. The obtained scene model and virtual scene are rendered simultaneously to obtain the real and virtual fusion scene. Analysis of experimental results shows that the proposed method can effectively realize augmented reality-holographic stereogram.